Thinking the US South : Contemporary Philosophy from Southern Perspectives - Sullivan, Shannon, 1967- (Book collections on Project MUSE., 2021)
"This anthology demonstrates that US Southern identities, borders, and practices play an important but unacknowledged role in ethical, political, emotional, and global issues connected to knowledge production"--